Mapping peat thickness and groundwater level using a portable electromagnetic instrument in Indragiri Hilir, Riau, Indonesia - Sutikno, Sigit; Yusa, Muhamad; Kusairi, Muhammad; Hendri, Andy; Muhammad, Ahmad; Qomar, Nurul (Journal of Degraded and Mining Lands Management, 2025)
Peatlands play a crucial role in the global carbon cycle, water regulation, biodiversity conservation, research, education, and recreation. Peat thickness and groundwater level (GWL) are key parameters for optimizing these peatland functions; therefore, mapping peat thickness and GWL quickly, accurately, and cost-effectively is essential. This study applied a geophysical survey using a portable electromagnetic instrument to estimate peat thickness and GWL. The instrument, which is simple to operate and wirelessly connected to a mobile phone, enables rapid measurement and visualization of subsurface resistivity. A research site in Indragiri Hilir Regency, Riau Province, Indonesia, was picked up as an experiment site to test the instrument. Three transects with measurement path lengths of 100 m each and a distance of about 1.4 km each were designed for the experiment. To validate the resistivity data against subsurface stratigraphy, core sampling was conducted at three points along each transect. The results demonstrated that the electromagnetic method effectively identified the interface between peat soil and the underlying marine clay. Analysis revealed that the resistivity values for unsaturated peat, saturated peat, and saturated clay were 68-81 ohm m, 75-96 ohm m, and 82-115 ohm m, respectively. These findings suggest that GWL mapping and peat stratigraphy characterization can be accurately achieved using this method.